PEMODELAN PEMASANGAN PENYANGGA SEMENTARA MENGGUNAKAN PERANGKAT LUNAK PHASE 2 PADA HEADRACE TUNNEL CHAINAGE 265 M – 375 M DI PLTA TULIS KABUPATEN BANJARNEGARA, JAWA TENGAH - Lulu Febri Nugraha (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
Implementation of development Hydroelectric Power Plant (HEPP) Write a dam will be constructed of concrete type dam times Write Banjarnegara district. Water from the dam Write dams planned for suplesi plan Maung, by creating a tunnel from the dam Write Merawu towards Kali. Water from the tunnel entrance on the upstream dam plan Maung. Before the water reached the Kali Merawu, formerly used as power plant turbines. So the head race tunnel tunnel work. Making the tunnel is strongly influenced by the mass of rock above the tunnel or overburden. Modeling research purposes pit tunnel condition before reinstalling the system buffer and temporary buffer on the tunnel design using Phase2 software so that it can determine the type most suitable buffer while the tunnel chainage chainage 306 m and 347 m The method used in this study with experimental methods. Using the help of Phase2 software to help model some temporary buffer to buffer variations in the form of bolts while concrete and benton shoot. Determining whether or not the buffer is safe while the results of the use value of the total displacement, and finite element. From the use of one of these parameters the total displacement (total collapse), there is a scale from chainage 306 m and 347 m chainage have total displacement 0.0222129 and 0.0165611 m m. Of the total displacement that there are more than 0.005 m, then at chainage 306 m and 347 m chainage unsafe and finite element number is less than 4 then the class of models Masaa rocks found on the chainage is less than 4 including unsafe. Type of buffer used in the form of concrete shot but shows the total value of less than 0.005 m dispalcement then coupled with the type of buffer while steel. Modeling is done in class IIIa and IIIb rock mass unsafe. It is necessary to increase the zone of concrete screws are indicated collapse. Zones are shown by the broken keterdapatan finite element.